Enzymes from Extreme Environments and their Industrial Applications - Littlechild, Jennifer A. (Frontiers in Bioengineering and Biotechnology, 2015)
This article will discuss the importance of specific extremophilic enzymes for applications in industrial biotechnology. It will specifically address those enzymes that have applications in the area of biocatalysis. Such enzymes now play an important role in catalysing a variety of chemical conversions that were previously carried out by traditional chemistry. The biocatalytic process is carried out under mild conditions and with greater specificity. The enzyme process does not result in the toxic waste that is usually produced in a chemical process that would require careful disposal. In this sense the biocatalytic process is referred to as carrying out ‘green chemistry’ which is considered to be environmentally friendly. Some of the extremophilic enzymes to be discussed have already been developed for industrial processes such as an L-aminoacylase and a γ- lactamase. The industrial applications of other extremophilic enzymes including transaminases, carbonic anhydrases, dehalogenases, specific esterases and epoxide hydrolases are currently being assessed. Specific examples of these industrially important enzymes which have been studied in the authors group will be presented in this review.